2021
DOI: 10.1158/2643-3230.bcd-21-0044
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Analysis of the Multicellular Ecosystem in Viral Carcinogenesis by HTLV-1

Abstract: High-dimensional single-cell landscape of immune alterations during HTLV-1 infection and leukemogenesis identifies hallmarks of premalignant and malignant T-cell states and the accompanying shift of systemic immune state toward myeloid and immunosuppressive.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 34 publications
(50 reference statements)
2
33
0
Order By: Relevance
“…36 39 This study also verified that T-cell overexpression of PD-L1 can be transferred to surrounding lymphocytes and myeloid cells, thereby propagating PD-L1 upregulation and immune evasion. 39 Joo et al 40 further used scRNA-seq to analyze the clonality of CD4 + and CD8 + T cells in ATL, which revealed a prevalent Treg phenotype characterized by high expression of CCR4.…”
Section: Hpv-associated Cervical Cancers and Hnsccsupporting
confidence: 61%
“…36 39 This study also verified that T-cell overexpression of PD-L1 can be transferred to surrounding lymphocytes and myeloid cells, thereby propagating PD-L1 upregulation and immune evasion. 39 Joo et al 40 further used scRNA-seq to analyze the clonality of CD4 + and CD8 + T cells in ATL, which revealed a prevalent Treg phenotype characterized by high expression of CCR4.…”
Section: Hpv-associated Cervical Cancers and Hnsccsupporting
confidence: 61%
“…Moreover, it is believed that ATL cells exhibit low viral protein expression along with genetic alteration and epigenetic silencing [ 69 ], which can potentially attenuate the effect of NIR-PIAS. Recently, single-cell analysis has indicated increased expression of cell surface proteins such as CD73 and CD99 in ATL cells [ 70 ]. These proteins may be novel therapeutic targets for ATL cells with defective proviruses devoid of Env expression.…”
Section: Discussionmentioning
confidence: 99%
“…One plausible explanation is that Foxp3 + infected T cells can evade immune surveillance via the expression of immune checkpoint molecules such as CTLA-4, PD-1 and TIGIT and immunoregulatory cytokines including IL-35 and IL-10. The similarities and differences of immunosuppressive mechanism between Treg and HTLV-1-infected cells still require further understanding and further studies utilizing single-cell methods for precise immunophenotyping will provide more evidence on how HTLV-1 evade host immunity ( 78 , 79 ).…”
Section: Immune Escape Mechanisms Used By Htlv-1-infected Cells For P...mentioning
confidence: 99%
“…HTLV-1 is also known to modulate the expression of immune checkpoint molecules on the cell surface of infected cells for immune evasion. Several studies have shown that HTLV-1 infection upregulates both the expression of stimulatory and inhibitory immune checkpoint molecules and is further augmented by leukemic transformation and ATL progression ( 78 , 79 , 94 ). For instance, the viral protein Tax is involved in the overexpression of OX40 ( 95 , 96 ), a costimulatory molecule which promotes cellular proliferation, enhances cell survival and suppresses Treg activity ( 97 ).…”
Section: Malignant Transformation Of Infected Cells and Additional Me...mentioning
confidence: 99%
See 1 more Smart Citation